Electrophysiological insights into the processing of nominal metaphors - De Grauwe, Sophie (2010)
We used event-related potentials (ERPs) to examine the time-course of processing metaphorical and literal sentences in the brain. ERPs were measured to sentence-final (Experiment 1) and mid-sentence (Experiment 2) critical words (CWs) as participants read and made plausibility judgments about familiar nominal metaphors (“A is a B”) as well as literal and semantically anomalous sentences of the same form. Unlike the anomalous words, which evoked a robust N400 effect (on the CW in experiments 1 and 2 as well as on the sentence-final word in experiment 2), CWs in the metaphorical, relative to the literal, sentences only evoked an early, localized N400 effect that was over by 400 ms after CW onset, suggesting that, by this time, their metaphorical meaning had been accessed. CWs in the metaphorical sentences also evoked a significantly larger LPC (Late Positive Component) than in the literal sentences. We suggest that this LPC reflected additional analysis that resolved a conflict between the implausibility of the literal sentence interpretation and the match between the metaphorical meaning of the CW, the context and stored information within semantic memory, resulting from early access to both literal and figurative meanings of the CWs.